Rubella immunity in native Turkish and Syrian immigrant pregnant women between 2010-2018 - Yucel Celik, Ozge; Aksu, Gönül; Obut, Mehmet; Keleş, Ayşe; Gültekin Çalık, Mine; Dağdeviren, Gülşah; Sahin, Dilek; Yücel, Aykan (The European Research Journal, 2022)
Objectives: The study has aimed to investigate the rubella immunity in native-Turkish and Syrian-immigrant pregnant women in Turkey. Methods: Between September 2010 and December 2018, the hospital records of pregnant patients were evaluated retrospectively. For each year, for the number of patients who were screened for rubella IgG and/or IgM antibodies, IgG avidity (if any), and PCR tests (if any) were investigated, and subjects were categorized by nationality. Results: During the study period, a total of 80,302 pregnant were tested with at least one of the rubella IgM or IgG antibodies. Of these, 22,962 pregnant women were screened for both IgG and IgM, 24,684 were screened for IgG, and 78,580 pregnant women were screened for IgM rubella antibodies. The seropositivity rate of IgG rubella antibodies in native and Syrian pregnant groups was 93.8% and 95.9%, respectively. In both groups, the IgM rubella antibodies were found as 0.5%. IgG avidity was investigated in 252 patients, whose test results were positive for IgM and IgG; and a low IgG avidity was detected in 5 native patients, while none was detected in the Syrian group. Conclusions: In the Syrian immigrant group, the susceptibility to Rubella is low, and it does not differ from the native Turkish population.